The Effectiveness of Android-Based Media in Chemistry Learning to Improve Chemistry Literacy and Learning Motivation (International Journal of Active Learning, 2023)
Research has been carried out on the development of android-based media in chemical learning to determine the feasibility ofandroid-based media reaction rate material in chemistry learning developed, and to know the influence of increasing chemical literacy skills and student learning motivation and knowing its effectiveness.This research is included in the type of Research and Development (RD research) by referring to the 4D model, namely defining (define), planning (design), development (develop) and disseminate (disseminate). The validation of android application media products is done by two media experts and two material experts. The media quality assessment of the developed android application was carried out by 4 chemistry teachers and three peer reviewers. The research subjects used were class XI students of SMA Nurul Muslim Batealit Jepara. The limited trial of media developed was carried out to determine the readability of the media to students who were not samples, the trial of learning motivation questionnaires and the trial of test questions using chemical literacy indicators to students in Class XII MIPA SMA Nurul Muslim Batealit, Field tests using 2 classes XI MIPA SMA Nurul Muslim Batealit in learning chemistry material reaction rate. Data collection was carried out using media assessment questionnaires, learning motivation questionnaires, chemical literacy test questions. The results showed that the media that had been developed showed that there was a major influence on improving chemical literacy skills andmoderate influence on increasing student learning motivation.